2011
DOI: 10.1097/scs.0b013e31820fe1f0
|View full text |Cite
|
Sign up to set email alerts
|

Oral Mucocutaneous Diseases

Abstract: Oral mucocutaneous diseases (MCDs) are a heterogeneous group of disorders that could involve oral mucous membrane frequently. The purpose of this study was analysis of clinicopathologic features and relative frequency of MCDs with emphasize on malignant transformation of oral lichen planus (OLP). In this retrospective study, clinical data regarding to site of involvement, patient's age and sex, and accompanied symptoms were noted, and pathologic slides of OLP were reviewed for the detection of dysplastic chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…About half of our patients reported substantial pain or discomfort related to their disease. This finding is in accordance with other studies in which a high proportion of OLP patients were symptomatic (2,28). We observed patients with two or more sites affected by lichen planus and extraoral involvement of lichen planus was seen in approximately one out of five patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…About half of our patients reported substantial pain or discomfort related to their disease. This finding is in accordance with other studies in which a high proportion of OLP patients were symptomatic (2,28). We observed patients with two or more sites affected by lichen planus and extraoral involvement of lichen planus was seen in approximately one out of five patients.…”
Section: Discussionsupporting
confidence: 93%
“…The World Health Organization has described oral lichen planus (OLP) as a precancerous disease (1) that may involve the mucous membrane and skin of various areas (2). A predominance of OLP in women, commonly occurring in the 6th and 7th decades of life, has been reported (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…In our meta-analysis we also noted that studies in which patients were followed for longer periods, reported significantly higher rates of malignancy vs. those that followed their patients for shorter periods or did not communicate their follow up periods; it is logical that dysplasia can appear at any time during the evolution of OLP. Some authors continue defending in recent papers ( 20 ) a disease category under the term "lichenoid dysplasia"; Although this creates controversy and disagreement, some positive aspects must also be recognized, such as to reinforce the concept of the potentially malignant nature of OLP. From our point of view, the dysplastic appearance in the context of a lichenoid tissue response has in itself the value in risk prediction indicating or pointing towards an increased risk of oral cancer development in an individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…PV is one of the most common VBDs, which includes a group of autoimmune diseases that are potentially life-threatening and cause blisters and erosions on the skin and mucous membranes [4,5]. Pemphigus vulgaris oral lesions may present several months before skin lesions in more than half of the patients [6].…”
Section: Introductionmentioning
confidence: 99%